Lessons Learned Patricia Scotland's Strategic Leadership on Maritime Security in Commonwealth Member States - Oktaviandra, Yosyea; Prakoso, Lukman Yudho; Suwarno, Panji; Soemantri, Asep Iwa; Ruslinar, Meli; Faisal, Muhamad; Zahra, Raesha Syahnaz; Triyani, Triyani; Novitasari, Yussie (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
This article explores lessons learned from Patricia Scotland’s strategic leadership as Secretary-General of the Commonwealth, focusing on maritime security challenges in Member States in maintaining maritime security in the Commonwealth. Maritime security demonstrates a comprehensive and sustainable approach, emphasizing multilateral collaboration, capacity building, preventive diplomacy and environmental protection. Her contribution to strengthening maritime security in Commonwealth Member States has helped them address complex and transboundary threats, such as piracy, illegal fishing and climate change. Her inclusive and strategic approach creates maritime stability that supports the prosperity and security of small states, while ensuring that ocean protection remains a top priority.